Pengaruh Perubahan Arus Kas dan Profitabilitas Terhadap Return Saham Sebelum dan Selama Pandemi Covid-19 (Studi Pada Sektor Transportasi dan Logistik Yang Terdaftar Di Bei Periode 2017-2020) - Rafly Yanuar; Suji Abdullah Saleh (Indonesian Accounting Literacy Journal, 2022)
This study intend to determine the effect of changes in cash flow and profitability on stock returns in transportation and logistics sector companies listed on the Indonesia Stock Exchange for the 2017-2020 period. This research method is a quantitative method with the data source used is a documentary in the form of the company's financial statements. The data analysis method used descriptive statistical analysis, classical assumption test, multiple regression analysis, and hypothesis testing. Based on the test results, operating cash flow, investment cash flow, funding cash flow, return on assets, return on equity, and earnings per share simultaneously have an effect on stock returns. Investment cash flow partially has a negative and significant effect on stock returns. Return on equity has a positive and significant effect on stock returns, while operating cash flow, funding cash flow, return on assets, and earnings per share have no partial effect on stock returns.